Zeolitic Imidazolate Framework‐8 as pH‐Sensitive Nanocarrier for "Arsenic Trioxide" Drug Delivery. Issue 57 (13th September 2019) - Ettlinger, Romy; Moreno, Natalia; Volkmer, Dirk; Kerl, Kornelius; Bunzen, Hana
Abstract: Previous results revealed that arsenic trioxide might be used as promising therapeutic agent for the treatment of some solid tumours as atypical teratoid rhabdoid tumours (ATRT). However, in order to become an approved drug for solid tumour treatment, the active formulation has to get more efficient and feasible—but at the same time less toxic. One of the possibilities to achieve this dichotomy is to use nanomedicine tools. Herein, we report on the Zn‐based metal–organic framework ZIF‐8 ( Z eolitic I midazolate F ramework‐8) which turned out to be a promising candidate for the delivery of As III species. It conjointly features a high drug loading capacity and a prominent pH‐triggered release behaviour. As III ‐loaded ZIF‐8 nanoparticles coated and non‐coated with polyethylene glycol were studied by XRPD, IR, Raman, TGA, TEM, EDX, CHN‐elemental analysis, sorption analysis and ICP‐OES, and their cytotoxicity was evaluated in vitro. Abstract : Studies showed that ZIF‐8 nanoparticles released only a little As III ‐drug at the neutral pH, whilst a complete drug release took place at the more acidic pH value. In vitro cytotoxicity tests revealed that the loaded drug increased the material cytotoxicity against cancer cells, whilst not influencing the toxicity against fibroblast.